Executives’ IT background and corporate digital technology innovation: Evidence from Chinese microenterprises - Shuang Cao; Yingjue Wu (PLoS ONE, 2025)
This study examines how executives’ IT backgrounds affect corporate digital technology innovation, using panel data from listed companies between 2011 and 2021. Findings indicate that executives’ IT backgrounds significantly enhance corporate digital technology innovation, particularly in digital technology invention patents, where the effect is especially pronounced, and the results are robust. Mechanistic analysis suggests managerial myopia and executives’ attention to digital technology are key factors that allow executives’ IT backgrounds to promote corporate digital technology innovation. Further analysis shows executives’ IT backgrounds have a greater promotional effect on digital technology innovation in state-owned enterprises, non-IT sectors, firms with influential executives, and organizations with long-serving executives. Economic analysis reveals that executives’ IT backgrounds can improve corporate financial performance by enhancing digital technology innovation. This paper highlights the importance of executive IT human capital and provides insights into government and corporate talent recruitment policies.